Process development of 'dadih' preparation using xylitol as substitute sugar: effect on thermal and texture characteristics - Mohd Thani, Nurfatimah; Mustapa Kamal, Siti Mazlina; Taip, Farah Saleena; Ismail, Ismayadi (Engineers Australia, 2012)

(untitled)
‘Dadih’ is one of the popular Malaysian puddings and a trad itional food normally consumed as a dessert. Producing healthy ‘dadih’by replacing sugar (sucrose) content with xylitol will provide intense sweetness with fewer calories. The objectives of the present study are to determine the suitable range of process conditions on ‘dadih’ preparation and to investigate the effect of xylitol as substitute sugar on thermal and texture characteristics of ‘ dadih’ samples. This study focuses on second phase or cooking stage. In ‘dadih’ preparation, the compositions of substituted xylitol are varied from 0%, 50% and 100%. The effects of two process parameters were studied and they are cooking temperature (85, 90 and 95 oC) and cooking time (10, 15 and 20 minutes). It was found that the composition of sugar substitute and process parameters were highly affected the thermal and texture characteristics of ‘dadih’. The suitable process conditions to produce ‘dadih’ comparatively with commercial texture characteristics were selected at cooking time between 10 to 20 minutes and cooking temperature at 85°C to 90°C.